2008
DOI: 10.1089/dia.2008.0263
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Glycemic Measurements in the Critically Ill

Abstract: In critically ill adult patients, measurement of blood glucose using arterial samples is recommended. Using arterial blood, the Abbott FreeStyle blood glucose meter and the point-of-care blood gas analyzer (Bayer Chiron 865) were shown to be highly accurate instruments to measure arterial blood glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 14 publications
2
47
0
Order By: Relevance
“…Differences between the 2 groups were found only when we included arterial samples in the analysis (as in the previous studies). This finding could have important implications in treating critically ill patients because it supports studies such as those by Scott et al, 32 Lacara et al, 33 and Slater-MacLean et al, 34 who found that capillary blood glucose values were higher than the corresponding arterial blood glucose values, and NICE-SUGAR, 17 which recommended against use of fingerstick samples for analysis of blood glucose levels.…”
Section: Resultssupporting
confidence: 72%
“…Differences between the 2 groups were found only when we included arterial samples in the analysis (as in the previous studies). This finding could have important implications in treating critically ill patients because it supports studies such as those by Scott et al, 32 Lacara et al, 33 and Slater-MacLean et al, 34 who found that capillary blood glucose values were higher than the corresponding arterial blood glucose values, and NICE-SUGAR, 17 which recommended against use of fingerstick samples for analysis of blood glucose levels.…”
Section: Resultssupporting
confidence: 72%
“…In contrast, another investigator found that clinically significant differences existed in device performance for this patient population. Nevertheless, almost all glucose meter results fell within acceptable zones on a conventional consensus error grid (14 ). Such data would suggest that error grid analysis may not be optimal for evaluating devices used in critically ill populations.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have directly examined glucose meter performance when these devices are used to manage patients on tight glycemic control (8,(11)(12)(13)(14); however, interpretation of these studies has been confounded by the different approaches used to assess glucose meter accuracy. Clinical outcome studies relating meter accuracy to patient outcome during TGC would be ideal, although they require large numbers of patients and are resource intensive.…”
Section: © 2010 American Association For Clinical Chemistrymentioning
confidence: 99%
“…2 Fingersticks, which can be painful for the patient, may yield unreliable glycemic values when a point-of-care (pOC) glucometer with capillary sampling is used. [3][4][5][6] Although the pOC glucometer is of particular concern in patients with anemia, [7][8][9] it has been used in numerous studies. 10 In critically ill patients, pressure-monitoring systems connected to indwelling arterial catheters also allow repeated extraction of blood samples.…”
Section: Intervention Groupmentioning
confidence: 99%